Human Capital as Competitive Advantage: Empirical Evidence from Entities of Pakistan - et. al., Dr. Khurram Sultan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose of the study: Human capital’s important role for Competitive advantage has a higher degree to achieve success, prosperity, goodwill, and spirit of competition for any company. The purpose of the study is to find out and explain the relationship between human capital and competitive advantage and to identify the impact of human capital on competitive advantage among firms in Pakistan. Methodology: According to the variables of the study, we collected the data by using different methods. First, collect data by doing surveys and conduct interviews on human capital and competitive advantage. The second method is to create a questionnaire and distribute the questionnaire among the selected sample. The model used in this study is Regression, Factor, and reliability analysis that tells the relationship between two or more than two variables. The dependent variable in this study is a competitive advantage and the independent variable is human capital. Randomly selected the sample of 50 persons either work in the business sector or a business student. Main Findings: From results and discussion, it is concluded that Human capital asset has a strong impact on competitive advantage and create excellence for the company. Creation of competitive advantage through human capital asset bring organizational sustainability and continued success for the company. Competitive advantage based on human capital assets brings innovation and sustainability to the company’s work. Also, create a distinction in work. Application of this study: This study contributes toward the financial sector for policymakers in order to construct the best capital configuration of the firm. This study also suggests which element is having more importance while making the capital configuration of the firm. Originality of this study: Capital structure is a crucial issue for entrepreneurs and CEOs of any firm. A number of studies are available related to other industries but fewer studies are available related to the textile firms of Pakistan so this research work provides the technique while making the best capital configuration for textile firms of Pakistan.